Dietary supplementation of blend of organic acids and monoglycerides alleviated diarrhea and systemic inflammation of weaned pigs experimentally infected with enterotoxigenic Escherichia coli F18 - Sangwoo Park; Shuhan Sun; Supatirada Wongchanla; Ying Chen; Xunde Li; Yanhong Liu (Journal of Animal Science and Biotechnology)
Abstract Background The emergence of antibiotic resistant microorganisms associated with conventional swine production practices has increased interest in acid-based compounds having antimicrobial properties and other biological functions as nutritional interventions. Despite the interest in organic acids and monoglycerides, few studies have examined the effects of the combination of these acid-based additives in weaned pigs under disease challenge conditions. Therefore, this study aimed to investigate the effects of dietary supplementation with blend of organic acids and/or medium-chain fatty acid monoglycerides on intestinal health and systemic immunity of weaned pigs experimentally infected with an enterotoxigenic Escherichia coli (ETEC) F18 at 4-week of age. Results Dietary supplementation of organic acids, monoglycerides, or both organic acids and monoglycerides (combination) reduced (P < 0.05) the diarrhea frequency of ETEC F18-infected pigs throughout the experimental period (d −7 to 21 post-inoculation). This is consistent with the reduced (P < 0.05) proportion of β-hemolytic coliforms in feces observed for the organic acid and combination treatments on d 10 post-inoculation. Supplementation of organic acids, monoglycerides, or combination also reduced (P < 0.05) bacterial translocation in mesenteric lymph nodes on d 21 post-inoculation. Pigs fed with monoglycerides or combination had lower (P < 0.05) white blood cells on d 5 post-inoculation, and pigs fed the combination also had lower (P < 0.05) lymphocytes than pigs in control group. Monoglyceride supplementation increased (P < 0.05) white blood cells and neutrophils compared with control group on d 14 post-inoculation. However, supplementation with organic acid blend, monoglyceride blend, or combination did not affect growth performance in this experiment. Conclusions Supplementation with monoglycerides or organic acids alone or in combination improves the detrimental effects of ETEC F18 infection in weaned pigs, as indicated by reduced diarrhea, fecal shedding of β-hemolytic coliforms, and bacterial translocation, and thus enhancing disease resistance. Monoglycerides reduced the inflammatory response during peak infection, but their immunomodulatory and possible synergistic effects with organic acids need to be further investigated.